Verification of NAISS Model for Road Traffic Noise Prediction in Urban Areas - Prascevic, M.; Cvetković, D.; Mihajlov, D.; Petrović, Z.; Radičević, B. (Elektronika ir Elektrotechnika, 2013)
Background of mathematical model for prediction of road traffic noise called NAISS model is shown in this paper. The model has been created by extracting function relation among the equivalent noise levels and the traffic parameters collected by systematic traffic noise monitoring in urban areas of the city of Nis. Based on the analysis of three different variants of traffic noise prediction model, the model with three input parameters (the number of passenger vehicles, freight vehicles and buses) and one output (Leq) and two separate equations for two ranges of noise levels has been proposed as rather correctly for using in the urban areas of the city of Nis. In order to examine validity of formed model, it is carried out the comparative analysis of NAISS model and the other models available in literature and the verification of NAISS model based on data collected by traffic noise monitoring in urban areas of the city of Nis during the years 2008-2010. The good results obtained in the comparison with other prediction methods have been confirmed in the verification process of NAISS model. Scatter plot for model verification shown in this paper as well as the results of statistical analysis of the differences between measured and calculated data show the validity and enforceability of the NAISS model for traffic noise prediction in urban areas of the city of Nis. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.1294